(untitled) (Nordic Journal of African Studies, 2002)
This article looks at the western educated elite of Cape Coast as a factor of change regarding their influence on the traditional political institutions. It also examines the processes by which institutions like the Asafo, a typical traditional military unit, were virtually drawn into national politics as it pertained in Cape Coast. Much as the Asafo retained their fundamental structures as a traditional institution their time-honoured roles took on a more modern dimension. It was a veritable case of the Asafo approaching the precipices of a pressure group, and as it were, being drawn into the colonial political dynamism.